2022
DOI: 10.3390/foods11101453
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Rapid and Simple Technological Process to Increase Levels and Bioccessibility of Free Phenolic Compounds in Annurca Apple Nutraceutical Product

Abstract: Insoluble bound polyphenols (ISBP) are polyphenolic compounds linked to the food matrix with different interactions limiting both their water extractability and consequent bioaccessibility. The health-promoting potential of polyphenols is historically known and well-demonstrated; specifically, Annurca apple polyphenols were studied both in vitro and in vivo for their effect in controlling cholesterol plasma levels. The aim of the study was the preparation of nutraceutical products based on Annurca apple polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
6
12
1
1
Order By: Relevance
“…The data obtained are similar to those of a previous study conducted on lyophilised Annurca apples subjected to acidic treatment to enhance phenol extraction (0.088 AE 0.003 and 0.521 AE 0.051 mgÁg À1 of procyanidin B2 and chlorogenic acid, respectively) [27], indicating that maceration with only water may be a suitable alternative for the extraction of these compounds.…”
Section: Hplc-dad Analysissupporting
confidence: 86%
“…The data obtained are similar to those of a previous study conducted on lyophilised Annurca apples subjected to acidic treatment to enhance phenol extraction (0.088 AE 0.003 and 0.521 AE 0.051 mgÁg À1 of procyanidin B2 and chlorogenic acid, respectively) [27], indicating that maceration with only water may be a suitable alternative for the extraction of these compounds.…”
Section: Hplc-dad Analysissupporting
confidence: 86%
“…Moreover, the decrease in TG levels observed in the TN treatment groups may be justified both by the reported beneficial effects exerted by polyphenols on the management of hypertriglyceridemia [ 36 ] and by the positive response of plasma TG levels resulting from improved glycemic control, as described by scientific evidence [ 37 ]. In agreement with this hypothesis, our characterization of the TN polyphenolic profile performed by a validated HPLC-DAD method [ 38 ] highlights the high potential of this matrix in terms of polyphenol content [ 22 ]. In this sense, increasing evidence suggests a pivotal role played by oxidative stress in the pathogenesis of both types of DM [ 39 , 40 ] and the related beneficial role exerted by polyphenolic compounds [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 54%
“…The antioxidants-enriched diet consisted of the administration of a polyphenolic fraction, obtained through the application of a technological process (acid treatment), capable of freeing the insoluble bound polyphenols from Annurca apple food matrix and of increasing polyphenol bioaccessibility ( Maisto et al, 2022 ). It was added to drinking water at a dosage of 30 mg/b.w.…”
Section: Polyphenol Administrationmentioning
confidence: 99%
“…Previously, we observed that physical activity and a diet enriched with antioxidants individually have an important hypotensive effect, and the association showed a more prolonged, but not better, hypotensive effect than the single treatment ( Del Seppia et al, 2022 ). In the present descriptive study, we assessed the effects of a physical exercise program associated with a diet enriched with products based on Annurca apple polyphenolic fraction ( Maisto et al, 2022 ) on preventing microvascular damages due to cerebral hypoperfusion and reperfusion injury in spontaneously hypertensive rats (SHRs) in association or when administered alone.…”
Section: Introductionmentioning
confidence: 99%